REPRESENTASI HOMOSEKSUALITAS DALAM FILM SAUSAGE PARTY - Ernando Sukam; Dini Valdiani; Imani Satriani (Jurnal Penelitian Sosial Ilmu Komunikasi, 2019)
AbstractThe objective of this research is to know signs and meanings (sign, object, interpretant) of homoxeksual that exist in Sausage Party. This research used Semiotica Charles Sanders Peirces theory that famous with his triangle meanings and also used Azhari and Kencanas homoxeksual theory that included in sexual behavior. This research uses a qualitative descriptive research approach. In this research, researchers used data source triangulation thecnique. According Bungin (2007:257), data source triangulation doing by comparing and measuring level of trust an information that obtained by interview result and document that related to each other. Key informant in this research is a psychology and the triangulan is movie watcher. The result shows that some scenes in Sausage Party represents adjusted homoxesual and secret homoxeksual. Keywords : Homoxeksual, Sexual Behavior, Semiotic, Movie